ENPP1 processes protein ADP-ribosylation in vitro. - Palazzo, L; Daniels, C; Nettleship, J; Rahman, N; McPherson, R; Ong, S; Kato, K; Nureki, O; Leung, A; Ahel, I (Wiley, 2016)
ADP-ribosylation is a conserved post-translational protein modification that plays a role in all major cellular processes, particularly DNA repair, transcription, translation, stress response and cell death. Hence, dysregulation of ADP-ribosylation is linked to the physiopathology of several human diseases including cancers, diabetes and neurodegenerative disorders. Protein ADP-ribosylation can be reversed by the macrodomain-containing proteins PARG, TARG1, MacroD1 and MacroD2, which hydrolyse the ester bond known to link proteins to ADP-ribose as well as consecutive ADP-ribose subunits; targeting this bond can thus result in the complete removal of the protein modification or the conversion of poly(ADP-ribose) to mono(ADP-ribose). Recently, proteins containing the NUDIX domain - namely human NUDT16 and bacterial RppH - have been shown to process in vitro protein ADP-ribosylation through an alternative mechanism, converting it into protein-conjugated ribose-5'-phosphate (R5P, also known as pR). Though this protein modification was recently identified in mammalian tissues, its physiological relevance and the mechanism of generating protein phosphoribosylation are currently unknown. Here, we identified ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) as the first known mammalian enzyme lacking a NUDIX domain to generate pR from ADP-ribose on modified proteins in vitro. Thus, our data show that at least two enzyme families - Nudix and ENPP/NPP - are able to metabolize protein-conjugated ADP-ribose to pR in vitro, suggesting that pR exists and may be conserved from bacteria to mammals. We also demonstrate the utility of ENPP1 for converting protein-conjugated mono(ADP-ribose) and poly(ADP-ribose) into mass spectrometry-friendly pR tags, thus facilitating the identification of ADP-ribosylation sites.